Comparison of the Kinetics of Electron Transfer in the Diffusion Limit for the Singlet and Triplet Quenching of Eosin Y by Quinones - Bertolotti, Sonia Graciela (2013)
Electron transfer (ET) rate constants were determined by means of lifetime measurements for the fluorescence quenching and by laser flash photolysis for the triplet quenching of the dye eosin Y by benzoquinones in acetonitrile. The results represent a new aspect of the dependence of the rate constants with the driving force in the diffusion limit region. That is, the rate constants for singlet quenching in the highly negative region of DGet do not decrease as predicted by Marcus theory, but rather show a small positive dependence on the driving force. However, it is found that, in the same free energy range, the triplet rate constants are lower than those for the singlet process. They also increase with the exergonicity of the reaction, but the dependence with DGet is less marked than that found for the singlet reaction. Even at a Gibbs energy change of 1.0 eV the triplet quenching rate constants do not reach the theoretical diffusion limit. The results are analyzed using the current theories for diffusionmediated ET reactions.